What is the first step when rewriting y = 6x2 + 18x + 14 in the form y = a(x – h)^2 + k? a) y = 6(x + 1)^2 – 11 b) y = 6(x + 1)^2 – 10 c)y = 6(x + 1)^2 – 4 d) y = 6(x + 1)^2 – 16
Answers
Answered by
1
Answer:
like my answer plz. and follo
like my answer plz. and follo
like my answer plz. and follo
like my answer plz. and follo
like my answer plz. and follo
like my answer plz. and follo
like my answer plz. and follo
like my answer plz. and follo
like my answer plz. and follo
like my answer plz. and follo
like my answer plz. and follo
like my answer plz. and follo
like my answer plz. and follo
Step-by-step explanation:
like my answer plz. and follo
like my answer plz. and follo
like my answer plz. and follo
like my answer plz. and follo
like my answer plz. and follo
Answered by
1
Answer:
plz bhai mere ko brainlist kar do na
Similar questions